День Соборності України: історико-політологічні дискусії. Вип. 1 - Хмельницький інститут ПрАТ «ВНЗ «МАУП» (My University, 2014)
У збірнику наукових праць вміщено статті, виголошені на засіданні круглого столу "22 січня 1919 року – День Соборності України: історико-політологічні дискусії". Авторами статей розкрито історичний, політологічний, правовий аспекти Акту Злуки українських земель; у контексті сучасності висвітлено історичні події 1917–1920 років. The collection of scientific works contains articles presented at the round table meeting "January 22, 1919 - Day of the Unity of Ukraine: Historical and Political Discussions". The authors of the articles reveal the historical, political, and legal aspects of the Act of Union of Ukrainian Lands; in the context of modernity, the historical events of 1917–1920 are highlighted.